PERAN ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR ANAK DI DESA DALAM TANJUNG INTAN (STUDI KASUS ANAK KELAS V SDN 02 SELIMBAU) - Putry Angelina Restianti; Sulistyarini Sulistyarini; Izhar Salim (Universitas Tanjungpura, 2021)
AbstractThis study aimed to find out how, The Role of Parents in Raising a Child’s in Learning (A Case Study of a Class V SDN 02 Selimbau). The method in this study used is descriptive with qualitative forms of research. The source of this research is the parents in the villages in the district selimbau. The data-gathering technique in this study is through interviews, observations, and documentations, while the data-collection tool used is the guideline for interviews, observation and documentation. The analysis in the study is presented in a qualitative descriptive way by using the parents' four - person informers. The result show that: (1) The role of parents as motivator increasing interest in child study well categorized, this is proven with the parents always motivate her children to be diligent studying. (2) The role of parents as facilitators in increasing interest learning kids are good, this can be seen from facilities that was given to me by that good old man they include food, clothing, and shelter. (3) The role of the parent as the mediator in increasing interest in learning kids are pretty good, this stuff i can see the parents has good communication with her children.Keywords: Interest in Learning, Role, Parents